KH AHMAD DAHLAN'S THOUGHTS ABOUT THE MODERNIZATION OF ISLAMIC EDUCATION IN INDONESIA - Jusua Barus; Aji Pratama (RADJA PUBLIKA, 2021)
This type of research is this research including the type of library research (library research),namely research whose object of study uses library data in the form of books as a data source. This study uses a phenomenological approach with the data source used in this paper is KH Ahmad Dahlan's Thoughts About the Modernization of Islamic Education in Indonesia. towards which direction this nation is being led and led and to face a hopeful future. KH Ahmad Dahlan tried to sue the practice of Islamic education in his time. And to realize the idea of ​​renewal in the field of education, KH Ahmad Dahlan felt the need to establish an educational institution that was oriented towards modern education. namely by using the classical system. He combines the Dutch education system with the traditional education system integrally. The reason behind the emergence of the idea of ​​modernizing KH Ahmad Dahlan's Islamic education, which arose due to two internal and external factors. Internal factors related to the Islamic educational institution itself and its elements. External factors are the most dominant external factors in influencing and contributing to the dynamics of Islamic educational institutions. Namely because of social politics and socio-culture. Contribution of thoughts KH